Functional Movement Screen scores in a group of division IA athletes - Miller, J. M.; Susa, K. J. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: To determine mean values of the Functional Movement Screen scores in Division IA collegiate athletes. METHODS: One hundred sixty-one Division I collegiate athletes were recruited to participate in the study. The Functional Movement Screen was performed during pre-participation screenings prior to the beginning of the season. All athletes performed all seven tests and clearing tests as part of their participation. All the athletes were injury free at the time of testing. A x2 analysis was used to evaluate whether significant differences in the individual scores existed and t-test comparisons were conducted for the composite scores of the FMS and to examine if there were significant differences between genders. RESULTS: No significant difference was found between genders. The overall mean FMS score amongst players was 16.2±2.6. Female athletes scored highest on the active straight leg raise (2.64±0.54) and shoulder mobility (2.52±0.72) while their lowest scoring trials were trunk stability (1.95±0.25) and IL (2.25±0.59). Male athletes scored highest on the push-pp test (2.78±0.49) and active straight leg raise (2.47±0.62) and the lowest on trunk stability (1.98±0.13). CONCLUSIONS: This study provides mean value scores for FMS scores when testing Division IA collegiate athletes. The FMS may be useful for recognizing deficiencies in movements.